Burden Among Caregivers of Patients with Parkinson Disease [Evaluación de la Sobrecarga en Los Cuidadores de Los Pacientes Con Enfermedad de Parkinson Ambulatorios y Sus Factores de Riesgo] - Chana-Cuevas, P; Alburquerque-Gonzalez, D (2013)
Background: Parkinson disease (EPI) patients often require being assisted by others. These caregivers are exposed to a decrease in their quality of life. Aim: To explore Parkinson disease patient features associated with a greater burden among their caregivers. Material and Methods: Fifty one patients with Parkinson disease (aged 67 ± 12 years, 29 men, with 8 ± 5 years of disease) and their caregivers, were studied. Patients were assessed with the Unified Parkinson Disease Rating Scale III, the Hoehn & Yahr stage standardization, Parkinson s minimental test, the neuropsychiatric inventory and the Beck Depression Inventory (IDB). The Zarit Burden Interview (ESZ) was applied to caregivers. Results: According to IDB, 45% of patients whose caregivers presented little or no burden had a depression, compared to 78% of those whose caregivers had moderate or intense burden. (p < 0.01). The ESZ score of caregivers correlated significantly with Parkinson patients age, IDB and axial involvement in the UPDRS-III (correlation coefficients of 0.4 p < 0.01, 0.6 p < 0.01 and 0.46 p < 0.01, respectively). Conclusions: Motor alterations, cognitive impairment and most importantly depression of patients with Parkinson disease are deteminants of burden for their caregivers.